Comparison of cost and return between paddy production and rice seeds production of Ban Na Ngam rice mill community enterprise in Chachoengsao province of Thailand - Topphak, P.; Khermkhan, J.; Suwanmaneepong, S. (My University, 2023)
The rice production classified to produce paddy for sale and consumption and grow rice to produce rice seeds. When comparing the cost of return of both productions, it was found that the rice seed production members had an average income net was 4,995.90 baht per rai, an average profit net was 3,496.04 baht per rai and an average cost net was 1,499.66 baht per rai. The paddy production members had an average income net of 4,234.11 baht per rai, an average profit net of 1,943.89 baht per rai, and an average cost net of 1,943.89 baht per rai. The information showed that the rice seed production member had an average cost net at a lower level than the cost net of the paddy production member. Most of the production costs come from the variable costs with the higher level of proportions for both members, except the variable costs that the paddy production members had the higher level from the spending on chemical pesticides.
Keywords: Community enterprise; Costs and return; Rice seeds